Bjorka’s Cybercrimes from the Perspective of Fiqh Jinayah - Zaky Anggara; Mohamad Sar'an; Enceng Arif Faizal; Muhammad Akbar Khan (Alhurriyah, 2026)
This study aims to analyze Bjorka’s cybercrimes from the perspective of Islamic criminal law (fiqh jināyah) by examining the concept of criminal liability (al-mas’ūliyyah al-jinā’iyyah) and formulating a classification of sanctions (ʿuqūbāh) applicable to contemporary cyber offenses. The study employs normative legal research using a descriptive-analytical approach through the examination of primary sources of Islamic law, classical and contemporary fiqh literature, statutory regulations, and relevant academic publications, which are analyzed qualitatively to construct a legal framework for addressing cybercrime. The findings reveal that Bjorka’s cyber activities constitute jarīmah taʿzīr because no explicit textual provisions prescribe specific punishments for hacking and related cyber offenses, although such acts embody prohibited elements of al-kadhib (falsehood), akhdh al-māl bi ghayr ḥaqq (unlawful appropriation of property), tajassus (unauthorized surveillance), and violations of the objectives of Islamic law (maqāṣid al-sharīʿah). The study further classifies taʿzīr sanctions into light, moderate, and severe categories based on the nature of the offense, the degree of harm, and its impact on individuals, society, and state security. The study concludes that the principles of fiqh jināyah provide a flexible normative basis for addressing contemporary cybercrimes through proportional taʿzīr sanctions while maintaining justice, deterrence, and public welfare. This research contributes a systematic framework for assessing criminal liability and classifying sanctions for cybercrime within fiqh jināyah, thereby strengthening the theoretical development of Islamic criminal law in responding to emerging digital crimes and supporting future cybercrime policy formulation.